Herbal Toothpastes as Desensitizing Agents: A Review - Kandasamy Parimala, Yuvarani; Sankeshwari, Roopali M.; Ankola, Anil V.; Ragu , Kavitha; Shankkari , Siva (Indian Journal of Integrative Medicine, 2025)
Dentinal hypersensitivity (DH) is a common dental disorder in which brief, stinging pain occurs due to exposed dentin reacting to thermal, tactile, or chemical stimuli. In approximately one-third of adults, DH has a notable effect on quality of life and is often associated with enamel erosion, gingival recession, and periodontal treatment. Pain results, based on Brännström’s hydrodynamic theory, from fluid movements in open dentinal tubules that activate nerve endings. Traditional desensitizing substances like potassium nitrate, stannous fluoride, and arginine-calcium carbonate exert their action either by nerve desensitization or tubule occlusion. Side effects and long-term safety concerns, though, have produced interest in more natural alternatives to traditional desensitizing materials. Plant-containing herbal toothpastes with cloves, neem, guava, and green tea provide plant-based ingredients anti-inflammatory, antimicrobial, and analgesic properties. These spices not only alleviate symptoms by soothing nerves and anti-inflammatory effects but can also contribute to dentinal tubule occlusion, offering a promising, safer option for controlling dentinal hypersensitivity.